Detection of Mycoplasma hyopneumoniae in piglet processing fluids. (26th October 2019) - Vilalta, Carles; Sanhueza, Juan Manuel; Murray, Deborah; Johnson, Levi; Pieters, Maria
Abstract : Processing fluid (PF) is a sample type composed of fluids obtained from testicles and tails as the product of piglet processing. Mycoplasma hyopneumoniae is a bacterium that colonises the respiratory tract of pigs and has rarely been detected in tissues outside the respiratory system. No data exist in the literature regarding detection of M hyopneumoniae in PF or its use for herd monitoring of this pathogen. The main goal of this study was to evaluate the feasibility of detecting M hyopneumoniae in PF. Testicles and tails of 21 conveniently selected litters from a commercial sow farm were collected, by litter, and tested for M hyopneumoniae by real time‐PCR. Daily aggregated processing tissues were collected for a two‐month period to assess the detection of M hyopneumoniae in PF. The comparison in the percentage of positive samples in fluids from testicles (38 per cent, 8/21) or tails (4.8 per cent, 1/21) was significantly different (P=0.023). The percentage of daily aggregated PF with cycle threshold values up to 37 was 52.9 per cent (9/17) and 26.7 per cent (4/15) for December and January, respectively. Overall, these data show detection of M hyopneumoniae in PF for the first time and points at the potential use of this sample for monitoring of this bacterium in breeding farms.